Research on audience news and information behavior in the application on mobile phone in Chongqing - Wang, Mengqi; Sukpasjaroen, Khunanan (Edelweiss Applied Science and Technology, 2024)
In the era of rapid advancements in mobile phone media, media integration has progressed into a stage where audience-centred market integration prevails, rendering the exploration of audience information behaviour[1] a paramount priority for both communication research and media practice. This paper delves into news information behaviour within the mobile media landscape, leveraging T.D. Wilson's information behaviour theory [2] as a starting point. It integrates theories such as Uses and Gratifications, Japanese information behaviour theory, media dependency theory, innovation diffusion theory, and consumer behaviour theory [3] to devise a communication information behaviour model. Through interdisciplinary theoretical linkages, this study aims to contribute to theoretical innovations in exploring the behaviour of communication audiences. Utilizing a robust foundation of literature reviews, the primary research methods employed are quantitative research and surveys. Data analysis is conducted using statistical software to discern the characteristics of audience news information behaviour in the mobile media environment. Furthermore, the study compares and contrasts the information behaviour patterns among typical users across different news audience segments. By synthesizing interview insights, the key factors influencing audience news information behaviour are identified, leading to the formulation of a communication news information behaviour model. Employing structural equation modelling (SEM)[4] techniques and statistical software, this paper delves into the intricate relationships between variables that influence the adoption behaviour of mobile news, ultimately constructing a mobile news adoption behaviour model.